2012
DOI: 10.1161/strokeaha.111.633958
|View full text |Cite
|
Sign up to set email alerts
|

The Albumin in Subarachnoid Hemorrhage (ALISAH) Multicenter Pilot Clinical Trial

Abstract: Background and Purpose Human albumin has been shown to exert neuroprotective effects in animal models of cerebral ischemia and humans with various intracranial pathologies. We investigated the safety and tolerability of 25% human albumin (ALB) in patients with subarachnoid hemorrhage (SAH). Methods The ALISAH (Albumin in Subarachnoid Hemorrhage) Pilot Clinical Trial was an open-label, dose-escalation study. We intended to study 4 different dosages of ALB of increasing magnitude (0.625 g/kg: tier 1; 1.25 g/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 36 publications
0
62
0
2
Order By: Relevance
“…Primarily, cerebral perfusion pressure should be maintained by intracranial pressure control, and then systemic blood pressure is lowered to decrease peripheral vascular resistance; inotropic action is increased using dobutamine and other agents; and preload such as volume expansion is increased, for example, by loading the appropriate amount of albumin. 30 In this study, the incidence of DCI did not differ significantly between the good grade and poor grade groups, but the incidence of symptomatic cerebral vasospasm was significantly lower in the poor grade group (Table 1). This was because many patients in the poor grade group could not be neurologically evaluated because of impaired consciousness.…”
Section: Discussionmentioning
confidence: 46%
“…Primarily, cerebral perfusion pressure should be maintained by intracranial pressure control, and then systemic blood pressure is lowered to decrease peripheral vascular resistance; inotropic action is increased using dobutamine and other agents; and preload such as volume expansion is increased, for example, by loading the appropriate amount of albumin. 30 In this study, the incidence of DCI did not differ significantly between the good grade and poor grade groups, but the incidence of symptomatic cerebral vasospasm was significantly lower in the poor grade group (Table 1). This was because many patients in the poor grade group could not be neurologically evaluated because of impaired consciousness.…”
Section: Discussionmentioning
confidence: 46%
“…115 In an openlabel doseescalation trial of intravenous human albumin, patients with SAH tolerated up to 1.25 g/kg per day of albumin and, at this dose, showed a trend towards improved outcome. 116 Erythropoietin was neuroprotective in animal models of ischaemic stroke, prevented loss of autoregulation after SAH in rats, 117 and reduced angiographic vaso spasm and delayed neurological deterioration, and improved outcome after SAH in rabbits. 118 The com pound inhibits apoptosis and stimulates neuro genesis and angio genesis.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Indeed, administration of albumin has been associated with improved outcomes in SAH beagle dogs (9) and in patients (10). More recently, the Albumin in Subarachnoid Hemorrhage (ALISAH) pilot study revealed that 1.25 g/kg/d albumin treatment is safe in patients with SAH and may produce a better outcome (11). However, the full-scale preclinical characteristics of albumin in SAH and its potential mechanisms have not been defined.…”
mentioning
confidence: 99%